Towards Generating P-Contrastive Explanations for Goal Selection in Extended-BDI Agents - Jasinski, Henrique; Morveli-Espinoza, Mariela; Tacla, Cesar Augusto (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
As agent-based systems have been growing, more and more the general public has access to them and is influenced by decisions taken by these systems. This increases the necessity for such systems to be capable of explaining themselves to a user. The Beliefs-Desires-Intentions (BDI) is a commonly used agent model that has an two-phase internal goal selection process (desires and intentions) to decide what goals to pursue. Belief-based goal processing (BBGP) model is an extended-BDI model whose selection process consists of four phases. This more-grained behavior may have relevant consequences for the analysis of what an intention is and better explain how an intention becomes what it is. Contrastive explanations are commonly employed by people and can bring benefits to the explanation exchange process. A Property-contrast (P-contrast) explanation is a type of contrastive explanation that compares the properties of an explanation object. Thus, we can take a goal as the object about which we want an explanation and its status in the selection process (that is, how much it has advanced) as a property. This work tackles the problem of generating P-contrast explanations and proposes a method to construct them. The method consists of two phases, which in turn consist of a set of steps. The first step of the second phase returns a set of beliefs that constitute a future explanation. Thus, this work focuses on the first phase and the first step of the second phase. We use a scenario of the cleaner world in order to illustrate the performance of our proposal.